Recognition of the Causative Agent of "Phossy Jaw" and "Fragile Femur" in Fumes Arising from White Phosphorus - Hinshaw, William Banks; Quin, Louis DuBose (Phosphorus, sulfur, and silicon and the related elements, 2015)
Exposure to the fumes and smoke from white phosphorus pastes in the strike-anywhere match industry was associated, in the latter half of the 19th century, with a low incidence of necrotic lesions of the jaw bones and/or a fragility of the mid-femur occasioning fractures after minor trauma. Hundreds of cases were reported in many countries. The plight of these workers was the subject of international social pressure eventually leading to the prohibition of the matches. The reappearance in the early 21st century of two similar maladies associated with bisphosphonic acid (BP) medications led us to investigate the potential connection between these two pairs of debilitating effects. The BP molecules were chosen for development beginning in the early 1970s as pharmacologically satisfactory analogs of a simple inorganic phosphorus compound, pyrophosphoric acid, which had been found to exert an inhibitory effect on bone dissolution in vitro. These BPs inhibited bone loss in vivo. Independently, chemical analyses published in the mid-1980s demonstrated that the original small inorganic phosphorus model molecule was the most prevalent substance in the complex fumes and smoke associated with the pair of legacy diseases, thus persuasively connecting it, mediated by a common biological mechanism, to the modern drug side-effects.